Binding characteristics of copper and lead in soil particulate organic matter - WANG Li-ping; ZHENG Shun-an; ZHANG Ming-kui (浙江大学学报. 农业与生命科学版)
In order to understand the enrichment mechanism of heavy metals in soil particulate organic matter (POM), four chemical species of Cu and Pb in the POM, including exchangeable, complex, organic tightly bound and mineral bound, were characterized by chemical selective extraction. As compared with <0.05 mm soil fraction, the POM had higher percentages of exchangeable, complex, organic tightly bound Cu and Pb. The percentage of the metals as exchangeable form decreased with decreasing size of the POM, while that of complex metals increased with decreasing size of the POM. There was a greater percentage of organic tightly bound Pb and Cu in the POM separated from polluted soils. However, additive Cu and Pb was mainly transformed into complex and exchangeable forms. It was suggested that enrichment of the metals in the POM not only could be residue after selective decomposition of plant residues which contained high concentrations of the metals, but also be formed through complex and exchangeable reactions between metals and the POM.